Literature Review - Pengaruh Kombinasi Model Flipped Classroom dan Model Problem Based Learning terhadap Kemampuan Pemecahan Masalah - Mariani, Dewi; Mustaji, Mustaji; Dewi, Utari (Akademika : Jurnal Teknologi Pendidikan, 2025)
Problem solving ability is one of the key competencies that students must have in the 21st century education era. However, traditional learning methods are often unable to equip students with the critical and analytical thinking skills needed to solve complex problems. This research aims to systematically evaluate the effect of the combination of Flipped Classroom and PBL on students' problem solving abilities through the Systematic Literature Review (SLR) method. Data was collected from various studies published in indexed journals over the last 10 years. Analysis was carried out to identify trends in research results, supporting factors and obstacles that influence the successful implementation of the combination of the two models. The research results show that the combination of Flipped Classroom and PBL has a significant positive impact on students' problem solving abilities. This model not only improves critical and analytical thinking skills but also supports the development of non-cognitive skills, such as collaboration and communication. In addition, the integration of technology in Flipped Classroom increases the flexibility and effectiveness of independent learning, which then strengthens the implementation of PBL in the classroom. However, challenges such as student and teacher readiness, access to technology, and appropriate learning design need to be considered to ensure successful implementation